Economic implication of COVID 19 on private sectors’ employees in Ibadan Metropolis, Oyo State, Nigeria - Serifat F. Akorede (African Journal of Behavioural and Scale Development Research, 2021)
The study examined the economic implication of COVID 19 on private sectors' employees in Ibadan Metropolis. The study used ex-post facto design of survey research type; purposive sampling technique was employed to select two hundred private sectors' employees from Ibadan city geographical zone in Oyo State. One compartmentalized, validated instrument was used to gather information in this research. This is: COVID 19 Economic Implication Questionnaire (r = 0.75). Four research questions were raised and answered. The data obtained were analyzed using Descriptive statistics (frequency and percentage count) and t-test at 0.05 level of significance. Results revealed that COVID 19 pandemic lockdown infinitesimally affect the purchasing power of private sectors' employees in Oyo State. Private sectors' employees are able to sustain their employment after the ease of COVID 19 lockdown. COVID 19 lockdown better the social interaction of private sectors' employees in Oyo State as majority of the respondents testified to the fact that they have substantial time to interact with their family. Significant difference exists between private sectors' employees living standard during (x = 20.85, Sd = 5.16) and after ( x = 21.93, Sd = 5.49) the ease of COVID 19 lockdown t =(df=199), 2.17, P = 0.032, The paper submitted that: government should formulate favourable policy that will increase the purchasing power of private sectors' employees, similarly, private sectors' employees should diversify in their skills to augment their source of income.